Case report: A rare case of imiquimod-induced atypical pemphigus vulgaris - Moro, Francesco; Ciccone, Davide; Fania, Luca; Mariotti, Feliciana; Salemme, Adele; Rahimi, Siavash; Pallotta, Sabatino; Di Zenzo, Giovanni (Frontiers in Medicine, 2022)
Background Pemphigus vulgaris is an autoimmune intraepithelial bullous disease involving the skin and the mucous membranes. Imiquimod, a topical therapy for skin basal cell carcinoma, is an amine that induces the production of tumor necrosis factor alfa, interleukin-1 and other cytokines. Pemphigus induced by drugs has been frequently reported, mostly after systemic therapy. Case presentation We present the case of a 50-year-old man who developed skin, intraoral and genital mucosae erosive lesions three days after a treatment with Imiquimod for multiple superficial basal cell carcinoma of the trunk. Direct and indirect immunofluorescence results were compatible with the diagnosis of pemphigus vulgaris. Enzyme-linked immunosorbent assay was negative for desmoglein 1 and 3, but interestingly, by immunoblotting on keratinocyte extracts a band of 170 kDa was obtained by IgG. The patient, after interrupting Imiquimod application, started a treatment with prednisolone and in four weeks showed a complete remission. Conclusion Topical Imiquimod therapy might induce pemphigus vulgaris in some patients. In the presence of multiple and large basal cell carcinoma, in order to reduce the risk of high absorption and adverse events, sequential treatment should be carried out.